Conjugates of Cryptophycin and RGD or isoDGR Peptidomimetics for Targeted Drug Delivery. Issue 6 (7th June 2019) - Borbély, Adina; Figueras, Eduard; Martins, Ana; Bodero, Lizeth; Raposo Moreira Dias, André; López Rivas, Paula; Pina, Arianna; Arosio, Daniela; Gallinari, Paola; Frese, Marcel; Steinkühler, Christian; Gennari, Cesare; et al.
Abstract: RGD‐cryptophycin and iso DGR‐cryptophycin conjugates were synthetized by combining peptidomimetic integrin ligands and cryptophycin, a highly potent tubulin‐binding antimitotic agent across lysosomally cleavable Val‐Ala or uncleavable linkers. The conjugates were able to effectively inhibit binding of biotinylated vitronectin to integrin αv β3, showing a binding affinity in the same range as that of the free ligands. The antiproliferative activity of the novel conjugates was evaluated on human melanoma cells M21 and M21‐L with different expression levels of integrin αv β3, showing nanomolar potency of all four compounds against both cell lines. Conjugates containing uncleavable linker show reduced activity compared to the corresponding cleavable conjugates, indicating efficient intracellular drug release in the case of cryptophycin‐based SMDCs. However, no significant correlation between the in vitro biological activity of the conjugates and the integrin αv β3 expression level was observed, which is presumably due to a non‐integrin‐mediated uptake. This reveals the complexity of effective and selective αv β3 integrin‐mediated drug delivery. Abstract : Successful delivery : Cryptophycin‐RGD/ iso DGR conjugates with lysosomally cleavable or uncleavable linkers display high binding affinity towards integrin αv β3 and show potent cytotoxicity in cell lines with different integrin expression levels.